Lack of Awareness of the Impact of Improperly Disposed Of Medications and Associated Factors: A Cross-Sectional Survey in Indonesian Households - Alfian, Sofa D.; Insani, Widya N.; Halimah, Eli; Qonita, Nabilla A.; Jannah, Siti S.; Nuraliyah, Nisa M.; Supadmi, Woro; Gatera, Vesara A.; Abdulah, Rizky (Frontiers in Pharmacology, 2021)
Introduction: Disposal of unused medications through environmentally unsafe routes is common in Indonesia. The lack of awareness of the impact of improperly disposed of medications is a significant contributing factor. The objectives of this study were to identify factors associated with lack of awareness of the impact of improperly disposed of unused medications and to assess the associations of awareness with medication disposal practices among the general population in Indonesia. Patients and methods: An observational cross-sectional survey was conducted using nonprobability sampling in Bandung, Indonesia, from November 2017 to January 2018 among respondents who were older than 18 years, had used any medication in the past, were literate, and had signed an informed consent document. Disposal practices and awareness regarding the impact of improperly disposed of unused medications were collected using an online- and a paper-based pre-validated questionnaire. The paper-based questionnaires were distributed to respondents in public places such as city center, markets, and religious places. Binary logistic regression was performed to assess associations of sociodemographic and other related factors with a lack of awareness. Odds ratios (ORs) with 95% confidence intervals (CIs) are reported. Results: Of 497 participating respondents, 433 and 64 respondents filled an online- or a paper-based questionnaire, respectively. Most respondents were female, aged between 18 and 30 years, and students/university students. Of 497 respondents, more than half (53.1%) were not aware that improper medication disposal could harm the environment and population health. Most respondents (79.5%) had never received information about proper medication disposal practices. The education level, the number of stored medications at home, and previous education about medication disposal practices were significantly associated with awareness of proper practices. In the multivariate analysis, only those with previous education about medication disposal practices were less likely to report a lack of awareness (OR: 0.043; 95% CI: 0.02–0.09). Respondents with a lack of awareness tended to dispose of their unused medications in the garbage or shared them with friends or relatives. Conclusion: There is a clear need to increase awareness of the importance of proper medication disposal practices, in particular among the student population of Bandung city, Indonesia. Healthcare providers can play an important role by educating this specific population on the proper disposal of unused medications.